Understanding human vulnerability to climate change : A global perspective on index validation for adaptation planning - Joern Birkmann and Ali Jamshed and Joanna M. McMillan and Daniel Feldmeyer and Edmond Totin and William Solecki and Zelina Zaiton Ibrahim and Debra Roberts and Rachel Bezner Kerr and Hans Otto Poertner and Mark Pelling and Riyanti Djalante and Matthias Garschagen and Walter Leal Filho and Debarati Guha-Sapir and Andrés Alegría (The science of the total environment, 2022)
Climate change is a severe global threat. Research on climate change and vulnerability to natural hazards has made significant progress over the last decades. Most of the research has been devoted to improving the quality of climate information and hazard data, including exposure to specific phenomena, such as flooding or sea-level rise. Less attention has been given to the assessment of vulnerability and embedded social, economic and historical conditions that foster vulnerability of societies. A number of global vulnerability assessments based on indicators have been developed over the past years. Yet an essential question remains how to validate those assessments at the global scale. This paper examines different options to validate global vulnerability assessments in terms of their internal and external validity, focusing on two global vulnerability indicator systems used in the WorldRiskIndex and the INFORM index. The paper reviews these global index systems as best practices and at the same time presents new analysis and global results that show linkages between the level of vulnerability and disaster outcomes. Both the review and new analysis support each other and help to communicate the validity and the uncertainty of vulnerability assessments. Next to statistical validation methods, we discuss the importance of the appropriate link between indicators, data and the indicandum. We found that mortality per hazard event from floods, drought and storms is 15 times higher for countries ranked as highly vulnerable compared to those classified as low vulnerable. These findings highlight the different starting points of countries in their move towards climate resilient development. Priority should be given not just to those regions that are likely to face more severe climate hazards in the future but also to those confronted with high vulnerability already.
Keywords: Climate change; Natural hazards; Societal impacts; Validity and applicability of indicators; Vulnerability